DHA supplementation during pregnancy does not reduce BMI or body fat mass in children: follow-up of the DHA to Optimize Mother Infant Outcome randomized controlled trial,. Issue 6 (30th March 2016) - Muhlhausler, Beverly S; Yelland, Lisa N; McDermott, Robyn; Tapsell, Linda; McPhee, Andrew; Gibson, Robert A; Makrides, Maria
ABSTRACT: Background: The omega-3 (n–3) long-chain polyunsaturated fatty acid (LCPUFA) docosahexaenoic acid (DHA) has proven effective at reducing fat storage in animal studies. However, a systematic review of human trials showed a lack of quality data to support or refute this hypothesis. Objective: We sought to determine whether maternal DHA supplementation during the second half of pregnancy results in a lower body mass index (BMI) and percentage of body fat in children. Design: We conducted a follow-up at 3 and 5 y of age of children who were born to mothers enrolled in the DOMInO (DHA to Optimize Mother Infant Outcome) double-blind, randomized controlled trial, in which women with a singleton pregnancy were provided with DHA-rich fish-oil capsules (800 mg DHA/d) or vegetable-oil capsules (control group) in the second half of pregnancy. Primary outcomes were the BMI z score and percentage of body fat at 3 and 5 y of age. Potential interactions between prenatal DHA and the peroxisome proliferator–activated receptor-γ ( PPARγ ) genotype as a measure of the genetic predisposition to obesity were investigated. Results: A total of 1614 children were eligible for the follow-up. Parent or caregiver consent was obtained for 1531 children (95%), and these children were included in the analysis. BMI z scores and percentages of body fat of children in the DHA group did not differ from those of children in the control group at either 3 y of age [BMI z score adjusted mean difference: 0.03 (95% CI: −0.07, 0.13; P = 0.61); percentage of body fat adjusted mean difference: −0.26 (95% CI: −0.99, 0.46; P = 0.47)] or 5 y of age [BMI z score adjusted mean difference: 0.02 (95% CI: −0.08, 0.12; P = 0.66); percentage of body fat adjusted mean difference: 0.11 (95% CI: −0.60, 0.82; P = 0.75)]. No treatment effects were modified by the PPARγ genotype of the child. Conclusion: Independent of a genetic predisposition to obesity, maternal intake of DHA-rich fish oil during the second half of pregnancy does not affect the growth or body composition of children at 3 or 5 y of age. This trial was registered at www.anzctr.org.au as ACTRN1260500056906 and ACTRN12611001127998.